Understanding marketing system for algae based biogas - Lohiraja, Janni (My University, 2018)
The world's energy consumption is expected to double in 2050 with a 1,6% annual growth rate. This has led to focus on finding alternative and renewable energy sources that support sustainable development. The purpose of this research is to form an understanding how the marketing system works for an algae based biogas. Research examines the barriers and opportunities of algae based biogas. The focus is on the empirical materials (interview data) and how the marketing system elements appear in the interviewee’s discussion. This research is related to the TransAlgae project which explores the possibilities for algae cultivation in the Nordic climate. One of the objectives of the project is to implement innovative solutions for producing micro- and macro-algae based biogas. The understanding of a marketing system started from creating the theoretical framework for marketing system for algae based biogas. Main theories are marketing system (Layton 2009), sustainable business model and PESTEL which form a theoretical framework of the study. The marketing system framework was enriched by the findings in empirical data. There are technological, economical, functional, knowledge, climate, cultural and legal barriers of algae based biogas. Algae cultivation and harvesting take more energy than the biogas can release is one example of technological barriers. There are functional, environmental and social opportunities for algae based biogas. Algae enhancing nutrient recycling is an example of environmental opportunity. There is enormous potential to make biogas from algae. The product is not close to commercialization even though algae have great properties as being most rapidly growing biomass and the ability to clean wastewater during cultivation. With the need of new renewable energy source and the great properties of algae it is essential to continue the research of algae based biogas.
Keywords: algae; biogas; marketing system; sustainable business model; fi=Markkinointi|en=Marketing|; fi=Markkinoinnin johtamisen maisteriohjelma|en=Master's Programme in Marketing Management|